Penanaman Nilai Mahabbah Rasulullah SAW bagi Kaum Remaja Melalui Kegiatan Membac Al-Barzanji di Desa Benerkulon Kecamatan Ambal Kabupaten Kebumen - Maryam Robi’atun; Hidayatu Munawaroh; Sofan Rizqi (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to describe the implementation of the al-Barzanji reading activity as a religious tradition in Benerkulon Village and analyze the strategy of instilling the value of love for the Prophet Muhammad (peace be upon him) among teenagers, including supporting and inhibiting factors. The study used a qualitative approach with a field research type. Data were collected through observation, interviews, and documentation, then analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the activity of reading al-Barzanji is carried out routinely by young people every Thursday night after the Isha prayer and serves as a means of preserving religious traditions as well as a medium for instilling the value of love for the Prophet Muhammad (peace be upon him). This activity also contributes to strengthening friendship, togetherness, and the development of Islamic artistic creativity among teenagers. The instillation of the value of love is carried out through role models, active involvement of teenagers in socio-religious activities, providing advice and motivation, and organizing interesting and participatory activities. Supporting factors include youth enthusiasm, support from religious leaders, a conducive social environment, and the availability of facilities, while inhibiting factors include busy teenagers, low interest of some teenagers, and the influence of technology and social media. These findings imply that strengthening local religious traditions can be an effective strategy in developing the character and spirituality of adolescents if managed adaptively and sustainably.